Implementasi Program Parenting Di Kelompok Bermain Cerdas Ceria Kota Serang - Titi Windiyanti; Fahmi Fahmi; Tri Sayekti (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to describe 1) parenting program implementation 2) benefits of parenting programs 3) supporting factors and inhibiting factors of parenting programs. The subjects of this study were principals, teachers and parents. Data collection using observation, interview and documentation techniques. The techniques used in data analysis are data reduction, data presen tation and conclusion drawing. Validity of data conducted to explain data using extended research, triangulation, membercheck and adequacy of references. The results showed that 1) The parenting program is carried out every three months with stages of planning, implementation and evaluation. Each theme is different, the first is about socializing school programs, the second is about maintaining the nutritional health of children and the third is about parenting in the digital era 2) this parenting program provides several benefits to respondents. 3) supporting factors include the enthusiasm of the participants, the solidarity of the committee, adequate facilities and infrastructure and the implementation time is not too long. Inhibiting factors include the lack of participants and the lack of school socialization.